경도 기반 조리 조건을 달리한 표고버섯의 산화방지 및 영양특성 연구 - 임소리(Sori Im); 천용기(Yong-Gi Chun); 양소정(Shaoting Liang); 한정아(Jung-Ah Han) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2018)
The textural and antioxidant properties, as well as the changes in functional constituents of shiitake mushrooms cooked by three different methods (boiling, steaming, and frying) were analyzed. The hardness of the mushrooms did not change significantly at the end time of cooking for each method. The antioxidant properties determined by measuring the free-radical scavenging activity and total phenolic content were the highest in the control (uncooked shiitake), and these properties were adversely affected after cooking, especially by boiling. Both the riboflavin and eritadenine contents were the highest in the control, but decreased upon cooking, in the following order: frying > steaming > boiling. The ergocalciferol content after frying was less than that in other samples. Although uncooked shiitake mushroom showed a higher concentration of functional constituents, it needs to be cooked adequately owing to its tough texture. If the hardness of the mushrooms cooked by different methods is the same, frying is considered the most acceptable method.